Impact of body mass index on the efficacy of endocrine therapy in patients with metastatic breast cancer - A retrospective two-center cohort study. (August 2018) - Zewenghiel, Luwam; Lindman, Henrik; Valachis, Antonis
Abstract: Bakground: The aim of this study was to investigate the impact of body mass index (BMI) on the efficacy of endocrine therapy in postmenopausal women with metastatic hormone receptor breast cancer (HR+BC) as well as to identify if the potential difference in efficacy was associated with Fulvestrant only or both aromatase inhibitors (AIs) and Fulvestrant. Methods: A consecutive cohort of postmenopausal women with HR+metastatic breast cancer that have received endocrine therapy including Fulvestrant as a metastatic treatment strategy at the Departments of Oncology in Eskilstuna and Uppsala, Sweden, between 2008 and 2016 were identified. The primary outcome of the study was time to disease progression (TTP) during the treatment with Fulvestrant in overweight and obese women compared to patient with normal BMI. Results: In total, 173 patients were enrolled in the study cohort, amongst these, 141 patients received both Fulvestrant and AIs and 32 received only Fulvestrant. No statistical significant association was observed between the three BMI categories and TTP, during Fulvestrant treatment (p = 0.136). The rates of objective response and clinical benefit due to Fulvestrant were similar among patients with normal weight, overweight and obesity, respectively. Conclusions: N o difference in treatment efficacy was seen between normal, overweight and obese women with metastatic HR+BC, when treated with Fulvestrant. Until further research with prospective studies is available, there is no evidence to support any modification in how Fulvestrant treatment is used in patients with metastatic breast cancer in regard to BMI. Highlights: We found no difference in endocrine treatment efficacy among normal, overweight, and obese patients with metastatic breast cancer. Comparable efficacy was found in both Fulvestrant and aromatase inhibitors regardless of BMI. Current endocrine treatment strategies for patients with metastatic breast cancer should be applied equally in patients regardless of BMI.